Nuchal Cord Encirclement & Birth Weight - Tahir Sayhood , Sumya (Tikrit Journal of Pharmaceutical Sciences, 2023)
Nuchal cord encirclement is defined as the condition in which the umbilical cord is wound at least once around the neck of the fetus. The ultrasound is one of the very helpful tools for evaluation of fetus with possible Nuchal cord entanglement, especially color flow Doppler ultrasonography which is a reliable tool to detect Nuchal coiling of the umbilical cord, and therefore color Doppler waveforms assessment in nuchal cord entanglements might be helpful for clinicians to decide a closer surveillance in labor by using intra-partum cardio-toco-graphy. The aim of the study was to determine if the presence of a single or multiple nuchal cord encirclement has a negative effect on fetal growth. This study was conducted at Tikrit Teaching Hospital. All live borns, single and multiple births during the study period (August 2008 to July 2009) were examined they were 3972 including term and preterm labor. Of them 271 have nuchal cord encirclement, of those 34 have multiple encirclement and 23 7 have single encirclement. The collected data were divided into those with encirclement and those without. The effect of nuchal cord on the birth weight according to the gestational age; sex of the neonate and the parity of the mother hc1s been evaluated. There was no significant association between the diagnosis of growth restriction and the presence of cord encirclement. The mean birth weight was not significantly different in the presence of a single or multiple nuchal cord encirclement than without encirclement. The conclusion was that whether the nuchal cord encirclement is single or multiple, it has no significant effect on birth weight.